Chronic Implant-Related Bone Infections—Can Immune Modulation be a Therapeutic Strategy? - Seebach, Elisabeth; Kubatzky, Katharina F. (Frontiers in Immunology, 2019)
Chronic implant-related bone infections are a major problem in orthopedic and trauma-related surgery with severe consequences for affected patients. Increasing antibiotic resistance and poor effectiveness of antibiotics against biofilm-forming bacteria reveal the necessity for alternative and innovative treatment approaches. Recently, the immune system has turned into focus of research, as it is a key player in infection defense and bone homeostasis, and targeted modulation of the host response becomes an emerging field of interest. The aim of this review was to summarize the current knowledge of impaired endogenous defense mechanisms that are unable to prevent chronification of bone infections associated with a prosthesis or osteosynthetic device. The presence of a foreign material adversely affects the immune system by generating a local immune compromised environment where spontaneous clearance of planktonic bacteria does not take place. Furthermore, the surface structure of the implant facilitates transition of bacteria from the planktonic to the biofilm life-form. Biofilm formation on the implant surface is closely linked to the development of a chronic infection, as an obviously misled adaption of the immune system fails to eventually eliminate biofilm infection. The interaction between the immune system and bone cells, especially osteoclasts, is extensively studied in the field of osteoimmunology and this crosstalk further influences bone homeostasis in favor of bone resorption, thus aggravating the course of bone infection. As T-cells become increasingly apparent to play a major role in chronic diseases, a special focus was set on what is known about an ineffective T-cell response. Myeloid-derived suppressor cells (MDSCs), anti-inflammatory macrophages, regulatory T-cells (Tregs) as well as osteoclasts are known to suppress immune defense mechanisms and negatively regulate T-cell-mediated immunity. Thus, these cells are considered as potential targets for immune therapy. The success of immune checkpoint inhibition in cancer treatment encourages the transfer of such immunological approaches into other chronic diseases and we discuss whether immune modulation can be a therapeutic tool for the treatment of chronic implant-related bone infections.